Letter from Dr. J. H. B. McClellan to James Curtis Booth - McClellan, John Hill Brinton (1861)
Dr. J. H. B. McClellan (1823-1874), a Philadelphian physician and brother of renowned civil war general, George B. McClellan (1826-1885), writes to the James Curtis Booth (1810-1888) to introduce a Mr. Hardcastle and provide recommendations for Hardcastle for a place of employment in the United States Mint.
Keywords: Booth, James Curtis, 1810-1888; United States Mint; Mint of the United States